Geological objects and structures in 3D - Frizon de Lamotte, Dominique; Leturmy, P. (Pascale); Souloumiac, Pauline; Frizon de Lamotte, Adrien (Boca Raton : CRC Press, 2020)
"Geologists must be able to "read" a geological map. That means interpreting the vertical dimension through the 2D view represented on the map and at different scales. The main objective of this book is to help students during this difficult learning process. Based on an abundant iconography (field photos, maps, cross-sections) and on basics in mathematics and mechanics, the book dissects the geometry of emblematic geological structures and objects in order to build 3 D models, printable in 3D. The book is dedicated to structural geology with a particular emphasis on kinematics of faulting and folding and on salt tectonics (chapters III, IV and V). The origin of continental great unconformities and oceanic break-up unconformities is also discussed (chapter II). The audience of the book is broad and includes (under)graduate students in Earth Sciences, professors of Natural Sciences, and professional or amateur geologists"--
Preface; Foreword; 1. Geology, a story of layers; 2. When strata overlie each other: the concept of unconformity; 3. When strata fracture, the faults; 4. When strata fold without breaking too much, detachment folds; 5. When folds and faults interact, fault-related folds and fold-and-thrust belts; 6. When the salt plays the major role, the effects of salt activity and the concept of salt tectonics; Appendix; Glossary; Stratigraphic Scale; References; Index
OCLC-licensed vendor bibliographic record.
Keywords: Geology -- Maps; TECHNOLOGY / Engineering / Civil